The oceanographic cruise of the USCGC GLACIER to the marginal sea-ice zone of the Chukchi Sea -- MIZPAC 78 - Paquette, Robert G.; Bourke, Robert H. (Monterey, California. Naval Postgraduate School, 1979)
This report presents the data and briefly describes the oceanographic results of the cruise of the USCGC GLACIER to the marginal sea-ice zone of the Chukchi Sea during the period l h to 28 July 1978. A brief analysis is presented which shows yearly recurring ice bays presumed to be due to bathymetric steering of warm currents. The relationship of upper and lower level temperature fronts to each other and their association with temperature f inestructure is described. Plots of temperature, salinity, density. Element: 62758N; Work: MR01549A09; Project: ZF52-555; Task: ZE52-555-001 supported in part by the Arctic Submarine Laboratory, Naval Ocean Systems Center, San Diego, California under Project Order Nos . 00002 and 00004 http://archive.org/details/oceanographiccru003paqu